Strengthening Village Cooperatives and MSMEs through the Thematic Entrepreneurship Seminar in Baji Pamai - Latief, Fitriani; Firman, Ahmad; Ilham, Bahrul Ulum; Asniwati, A.; Surianto, S. (Manunggal Halim Jaya, 2026)
This study aims to apply academic entrepreneurship research to practice by implementing a participatory thematic seminar that empowers Micro, Small, and Medium Enterprise (MSME) actors and strengthens economic institutions in Baji Pamai Village, Indonesia. The community service activity employed a participatory andragogical approach, including interactive presentations, focused group discussions, participatory potential mapping, and field observations. It was integrated into the Thematic Student Community Service Program (KKN-T) of Institut Teknologi dan Bisnis Nobel Indonesia, facilitating a Triple Helix collaboration between academia, village government, and the community. The intervention significantly raised participants' awareness and motivation for entrepreneurial development. Key outcomes included the co-creation of concrete, actionable ideas for professionalizing the Village-Owned Enterprise (BUMDes) and local cooperatives, with strategic focus areas such as product diversification based on local commodities (e.g., chili, ginger, forest honey), digital branding, and enhanced collaborative governance. The seminar validated the effectiveness of a 'working with the community' approach over a top-down model. The success underscores the critical role of thematic KKN as a mechanism for direct knowledge transfer and grassroots empowerment. However, it also highlights the necessity of sustained post-seminar mentoring. This ongoing support is not just beneficial but essential for ensuring the implementation of co-created ideas and should be a key consideration in future initiatives.